2008
DOI: 10.1002/cjoc.200890127
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Retention‐Activity Relationship Studies by Liposome Electrokinetic Chromatography to Predict Skin Permeability

Abstract: Liposome electrokinetic chromatography (LEKC) provides a simple and facile approach for drug membrane interactions using liposome as a pseudostationary phase. This study evaluated the potential of LEKC for high-throughput skin permeability profiled as an in vitro technique. A quantitative retention-activity relationship (QRAR) model for the estimation of skin permeability was proposed. For the 16 structurally diverse chemicals, lg k correlated well with permeability values (R 2 =0.886). The predictive ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…It was found that the predictive value of QSAR calculations was lower that that of QRAR (R 2 = 0.704). LEKC and QRAR can be successfully applied for the prediction of skin permeation capacity and for the screening of new compounds (Xian et al, 2008a).…”
Section: Liposome Electrokinetic Capillary Chromatographymentioning
confidence: 99%
“…It was found that the predictive value of QSAR calculations was lower that that of QRAR (R 2 = 0.704). LEKC and QRAR can be successfully applied for the prediction of skin permeation capacity and for the screening of new compounds (Xian et al, 2008a).…”
Section: Liposome Electrokinetic Capillary Chromatographymentioning
confidence: 99%
“…At present, there are several different methods that have been used to prepare liposome. 5,6 In this study, we report a study of a novel dexamethasone formulation by performing the controlled process of acute toxicity and anti-inflammation with dexamethasone sodium phosphate injection, dexamethasone palmitate liposome and dexamethasone palmitate long circulating liposome on mice.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with IAM and MEKC, LEKC provides not only the measurement advantages, such as speed, small sample amount, automation, lack of sample purity requirement, and high reproducibility, but also a distinct lipophilicity index in pharmacokinetic studies, as liposomes possess spherical lipid bilayer microstructures that make them more suitable models for the dynamic and fluid bilayer environment of biomembranes. LEKC has been used to evaluate the penetration of chemicals through skin in recent years and the derived quantitative structure–permeability relationship models showed adequate predictive ability for skin permeation, as log K p 9,10…”
Section: Introductionmentioning
confidence: 99%